P 47 The Impact of directional deep brain stimulation on subthalamic beta power in Parkinson's disease. (May 2022) - Kaplan, J.; Busch, J.L.; Schneider, G.H.; Kühn, A.A.
Abstract : Introduction : Beta power in subthalamic local field potentials (LFPs) is a well established biomarker for bradykinesia-rigidity in idiopathic Parkinson's Disease (IPS) and is a promising feedback signal for adaptive deep brain stimulation (DBS). However, the effect of directional stimulation on this biomarker has not yet been elaborated. With new DBS-systems allowing to combine directional stimulation with relatively artifact-free recordings of local field potentials (LFPs), we want to assess the impact of directionality on beta power and motor performance. Patients & Methods : So far, 6 IPS patients implanted with Medtronic SenSight directional electrodes in the subthalamic nucleus (STN) have been included in the study. LFPs were recorded post-operatively and during a 3 months follow up visit (3MFU) with the patient at rest using the Medtronic Percept PC implantable pulse-generator. Additionally, at the 3MFU, a monopolar review of all segmented contacts (separately and combined as ring) was carried out in the medication "off" state. A rotameter task was used to assess motor performance. Following each block consisting of 2 minutes of rest and 30 seconds of rotation, stimulation amplitude was increased stepwise up to a maximum amplitude of 3 mA or the occurrence of side effects. LFPs were streamed throughout the review. The primary outcome is the reduction of mean beta power with directional stimulation compared with (1) no stimulation and (2) ring stimulation. The secondary outcomes are: (1) Beta burst length distribution, (2) motor performance and (3) rate of side effects with directional compared to ring stimulation. Results : Further patient inclusion to a minimum of 10 patients is planned before the summit. Directional and ring stimulation led to dose-dependent reduction of mean beta power in the STN. Stimulation had an effect on both movement amplitude and velocity. In 4 out of 6 patients, the side effect threshold was higher with directional stimulation compared to ring stimulation. At the summit, we will also report changes in beta burst length distribution with directional compared to ring stimulation and the predictive value of beta power in postoperative intersegmental rest recordings for the clinically most effective directional contact. Conclusion : Our study contributes to characterizing LFP beta power in the context of directional stimulation and its relation to motor performance. This is a prerequisite for combining directional stimulation with beta-driven adaptive DBS, which ultimately could further improve DBS therapy.